How modified Delphi can help collect data from group of experts? - Ayob, Mohd Fairullazi (2019)
Invited and appointed by Deputy Dean of Post Graduate, KAED as a Guest Speaker to provide talk on a research methodology topic to Post Graduate students (Master and PhD)in Post Graduate workshop. Date: 10th April, 2019 Time: 11.15am-12.15pm Venue: Graphic Design Lab, KAED.